Characteristics of inline speedskating - Incremental tests and effect of drafting - Krieg, A.; Meyer, T.; Clas, S.; Kindermann, W. (International Journal of Sports Medicine, 2006)
Competitive inline speedskating combines a movement pattern similar to speedskating on ice with pack-oriented competition modes known from cycling. The deep-seated body position leads to high static load and, thus, restricted blood flow within propulsive muscles. This condition may affect lactate kinetics and limit V·O2peak. The present study compares physiologic reactions to graded cycling and skating exercise among top-level inline speedskaters and quantifies the effect of drafting. Eight male inline speedskaters of the top national level were examined. The study consisted of two graded exhaustive exercise tests (cycling and speedskating) and a pairwise drafting test. All tests were carried out with simultaneous gas exchange (MetaMax 2, Cortex, Germany) and heart rate measurements as well as determination of blood lactate concentrations. Maximal values of oxygen consumption (cycling: 4.91 ± 0.60; skating: 4.85 ± 0.50 l · min-1; p = 0.78), lactate concentration, or heart rate were similar for cycling and skating. At workloads corresponding to blood lactate concentrations of 4 mmol · l-1 oxygen uptake (cycling: 3.24 ± 0.65; skating: 3.97 ± 0.40 l · min-1; p < 0.05) and heart rate (cycling: 162 ± 9; skating: 173 ± 6 min-1; p < 0.05) were significantly higher during skating. The differences in heart rate ranged between - 2 and 23 min-1. The drafting effect was 15 ± 6 % at 30 km · h-1 (3.34 ± 0.19 vs. 2.83 ± 0.29 l · min-1) and 14 ± 5 % at 33 km · h-1 (3.87 ± 0.26 vs. 3.32 ± 0.27 l · min-1). During inline speedskating the attainment of V·O2peak is not impaired when compared to cycling exercise. However, the derivation of exercise prescriptions from a stepwise cycling test does not seem appropriate. The drafting effect of inline speedskating is within the range known from cycling.